2019
DOI: 10.1596/1813-9450-8794
|View full text |Cite
|
Sign up to set email alerts
|

Debt in Low-Income Countries: Evolution, Implications, and Remedies

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Often these instruments are perceived as alternative choices, but this paper finds there are important gains from deploying them jointly, provided countries have sufficient fiscal space. Debt levels are rising in many low-income countries (Essl et al 2019), and in such circum-stances it is preferable for climate policy to be financed by taxation or budget reallocation instead of deficit spending (Forni et al 2019). However, for advanced economies, Blanchard (2019) observes that sovereign debt, in contrast to corporate debt, is not rising that much, so there may be space for pursuing climate policies by green bonds and carbon pricing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Often these instruments are perceived as alternative choices, but this paper finds there are important gains from deploying them jointly, provided countries have sufficient fiscal space. Debt levels are rising in many low-income countries (Essl et al 2019), and in such circum-stances it is preferable for climate policy to be financed by taxation or budget reallocation instead of deficit spending (Forni et al 2019). However, for advanced economies, Blanchard (2019) observes that sovereign debt, in contrast to corporate debt, is not rising that much, so there may be space for pursuing climate policies by green bonds and carbon pricing.…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding these potential benefits, the use of green bonds can be problematic in countries with existing high public or private debt. Debt levels are rising in many low-income countries (Essl et al 2019), and in such circumstances it is optimal for climate policy to be financed by taxation or budget reallocation instead of deficit spending (Forni et al 2019). However, the greatest mitigation effort should be borne by the largest carbon emitters, which are mostly high and middle-income countries that have already issued green bonds.…”
Section: Role Of Green Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 A recent survey with 540 large investors reported that only 14% of them believed that current supply of ESG fixed income products is sufficient for the market, and that only 6.6% are satisfied with the current bond market penetration of ESG disclosures (RBC Global Assessment Management 2018). 13 Given that green bonds attract new socially responsible investors and asset managers, several issuers report the diversification of their investors base as a benefit of this type of security (OECD 2017, GIZ 2018). We can also observe this benefit for some governments and sovereign bond issuers (Climate Bonds Initiative 2018 and thereby allowing the displacement of emissions rather than their net reduction.…”
Section: Interaction Effects Of Carbon Pricing and Green Bondsmentioning
confidence: 99%